The fintech gender gap - Chen, S.; Doerr, S.; Frost, J.; Gambacorta, L.; Shin, H.S. (Journal of Financial Intermediation, 2023)
Can fintech close the gender gap in access to financial services? Using novel survey data for 28 countries, this paper finds a large and ubiquitous ‘fintech gender gap’: while 29% of men use fintech products, only 21% of women do. This difference exceeds the gender gap in bank account ownership at traditional financial institutions. While country characteristics and individual-level controls explain about a third of the fintech gender gap, the residual gap declines by 60% when accounting for gender differences in the willingness to use new financial technology, the suitability of fintech products, and the willingness to use fintech entrants if they offer cheaper products. The paper concludes by discussing drivers of differences in attitudes and implications for policy to foster financial inclusion with new technology.